Biosphere frontiers of subsurface life in the sedimented hydrothermal system of Guaymas Basin - Teske, Andreas; Callaghan, Amy V.; LaRowe, Douglas E. (Frontiers in Microbiology, 2014)
Temperature is one of the key constraints on the spatial extent, physiological and phylogenetic diversity, and biogeochemical function of subsurface life. A model system to explore these interrelationships should offer a suitable range of geochemical regimes, carbon substrates and temperature gradients under which microbial life can generate energy and sustain itself. In this theory and hypothesis article, we make the case for the hydrothermally heated sediments of Guaymas Basin in the Gulf of California as a suitable model system where extensive temperature and geochemical gradients create distinct niches for active microbial populations in the hydrothermally influenced sedimentary subsurface that in turn intercept and process hydrothermally generated carbon sources. We synthesize the evidence for high-temperature microbial methane cycling and sulfate reduction at Guaymas Basin – with an eye on sulfate-dependent oxidation of abundant alkanes - and demonstrate the energetic feasibility of these latter types of deep subsurface life in previously drilled Guaymas Basin locations of Deep-Sea Drilling Project 64.